The presence of busulfan metabolites and pharmacometabolomics in plasma drawn immediately before allograft infusion in hematopoietic cell transplant recipients - Jeannine S. McCune; Sandi L. Navarro; Linda J. Risler; Brian R. Phillips; Suping Ren; H. Gary Schoch; K. Scott Baker (Wiley, 2023)
Abstract Busulfan is hepatically metabolized through glutathione (GSH) conjugation; in vitro, this process depletes hepatocyte GSH stores and generates the cytotoxic metabolite γ‐glutamyldehydroalanylglycine, which is too unstable to be quantitated in vivo. We sought to evaluate if pre‐graft (i.e., immediately before allograft infusion) concentrations of busulfan metabolites' and of endogenous metabolomic compounds (EMCs) representing the glutathione pathway were associated with clinical outcomes in hematopoietic cell transplant (HCT) recipients receiving busulfan. The clinical outcomes evaluated were relapse, acute graft versus host disease (GVHD), chronic GVHD, non‐relapse mortality, and neutrophil nadir. In pre‐graft samples obtained from patients immediately before allograft infusion, our objectives were to evaluate for: (1) the presence of busulfan and its metabolites tetrahydrothiophenium ion (THT+), tetrahydrothiophene 1‐oxide, sulfolane, and 3‐hydroxysulfolane (N = 124); (2) EMCs using a global metabolomics assay (N = 77); and (3) the association of the busulfan metabolites and the EMCs with clinical outcomes. In the pre‐graft samples, busulfan and THT+ could not be detected. THT 1‐oxide, sulfolane, and 3‐hydroxysulfolane were quantitated in 9.6%, 26%, and 58% of pre‐graft samples; their concentrations were not associated with clinical outcomes. Four pre‐graft EMCs were statistically significantly associated with the neutrophil nadir. The pre‐graft EMCs were not associated with the other clinical outcomes. In conclusion, busulfan's metabolites are present in patients' plasma immediately before allograft infusion; the neutrophil nadir is associated with pre‐graft EMCs. Future research should investigate the association of clinical outcomes with the concentrations of busulfan's metabolites and EMCs in the pre‐graft plasma from allogeneic HCT recipients.